Predicting multiple victim versus single victim sexual abuse: an examination of distal factors and proximal factors associated with the first abuse incident. Issue 1 (2nd January 2016) - McKillop, Nadine; Smallbone, Stephen; Wortley, Richard
Abstract: Official and confidential self-report data on 83 convicted adult male sexual abusers were analysed to examine whether sexual offending progression can be better predicted from distal antecedents, or from proximal antecedents and outcomes associated with the first sexual abuse incident. Fifty-six offenders who sexually abused more than one victim (multiple victim offenders; MVOs) were compared to 27 offenders who sexually abused a single victim only (single victim offenders; SVOs). MVOs were younger at the time of their first sexual abuse incident, and were more likely to first abuse male and non-familial children. With the exception of sexual attraction to male children, no differences were found between the two groups on distal antecedents. Proximal antecedents and outcomes associated with the first sexual abuse incident were significantly related to multiple victim offending. Logistic regression analysis identified the presence of sexual difficulties in the month prior to the first abuse incident, and sexual excitement immediately preceding the first incident, as significant unique predictors. Implications for risk assessment and risk management are discussed, and future research directions proposed.